Wuzhi Capsule Dosage Affects Tacrolimus Elimination in Adult Kidney Transplant Recipients, as Determined by a Population Pharmacokinetics Analysis - Chen L; Yang Y; Wang X; Wang C; Lin W; Jiao Z; Wang Z (Dove Medical Press, 2021)
Lizhi Chen,1,* Yunyun Yang,1,2,* Xuebin Wang,1,* Chenyu Wang,2 Weiwei Lin,3 Zheng Jiao,2,4 Zhuo Wang1 1Department of Pharmacy, Shanghai Changhai Hospital, Naval Medical University, Shanghai, 200433, People's Republic of China; 2Department of Pharmacy, Shanghai Chest Hospital, Shanghai Jiao Tong University, Shanghai, 200030, People's Republic of China; 3Department of Pharmacology, The First Affiliated Hospital, Fujian Medical University, Fuzhou, People's Republic of China; 4Department of Pharmacy, Huashan Hospital, Fudan University, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Zheng JiaoDepartment of Pharmacy, Shanghai Chest Hospital, Shanghai Jiao Tong University, 241 Huaihai West Road, Shanghai, 200030, People's Republic of ChinaTel +86 21 2220 0000 ext 3021Email jiaozhen@online.sh.cnZhuo WangDepartment of Pharmacy, Shanghai Changhai Hospital, Naval Medical University, 168 Changhai Road, Shanghai, 200433, People's Republic of ChinaTel/Fax +86-21-31162299Email wztgyx223@163.comPurpose: In this study, we aimed to establish a tacrolimus population pharmacokinetic model and better understand the drug-drug interaction between Wuzhi capsule and tacrolimus in Chinese renal transplant recipients.Patients and Methods: We performed a population pharmacokinetic analysis using a non-linear mixed-effects model to determine the suitable Wuzhi capsule dose in combination with tacrolimus. Data on 1378 tacrolimus steady-state concentrations were obtained from 142 patients who received kidney transplant in Changhai Hospital and Huashan Hospital. Demographic characteristics, laboratory tests, genetic polymorphisms, and co-medications were evaluated.Results: The one-compartment model best described data. Our final model identified creatinine clearance rate, hematocrit, Wuzhi capsule dose, CYP3A5*3 genetic polymorphisms, and tacrolimus daily dose as significant covariates for tacrolimus clearance, with the value of 14.4 L h− 1, and the between-subject variability (BSV) was 25.4%. The Wuzhi capsule showed a dose-dependent effect on tacrolimus pharmacokinetics, demonstrating a stronger inhibitory effect than inductive effect.Conclusion: Our model can accurately describe population pharmacokinetics of tacrolimus when combined with different doses of Wuzhi capsule. Additionally, this model can be used for individualizing tacrolimus dose following kidney transplantation.Keywords: renal transplantation, inhibitory effect, one-compartment model, CYP3A5